EDUKASI DENGAN METODE PEER GROUP TERHADAP PENGETAHUAN DAN KETERAMPILAN RESUSITASI JANTUNG PARU PADA SISWA - Rugian, Miranda; Kerangan, Johanis; Sumilat, Vervando J. (Lasalle Health Journal, 2023)
Introduction: Cardiac arrest is a common cause of death, but many people are unaware of the signs and symptoms. This results in delays in requesting emergency assistance to start Cardiopulmonary Resuscitation (CPR). Teaching RJP to teenagers can improve skills and help create a society where mutual help is achieved. Objective: To determine the effect of education using the peer group method on the knowledge and skills of cardiopulmonary resuscitation among students carried out at SMK Negeri 06 Manado. Method: This research method is quantitative research using a Quasi experimental design with a control group (non-equivalent control group design). The intervention group will be given cardiopulmonary resuscitation education using the peer group method, while the control group will be given cardiopulmonary resuscitation education via leaflets with 20 students in each group. Data collection tools will use knowledge questionnaires and observation sheets related to cardiopulmonary resuscitation. Results: Wilcoxon test results for knowledge before and after intervention in the intervention group (p value 0.000) and control group (p value 0.075), while the skills results for the intervention group (p value 0.008) and control group (p value 1.000). Based on the results of the Mann-Whitney test, students' knowledge shows a p value of 0.000, while for skills the p value is 0.004. Conclusion: Providing education about cardiopulmonary resuscitation using the peer group method has an effect on increasing students' knowledge and skills. It is hoped that students can continue providing this cardiopulmonary resuscitation education to other friends using the peer group method